Sleep after Rhythmic Cold Effects - Ventskovska, O. A.; Shylo, O. V.; Babiychuk, G. A. (Problems of Cryobiology and Cryomedicine, 2011)
There were investigated the rhythmic cold effects (RCE) on the sleep-wake cycle. After RCE the hourly dynamics change of sleep and wakefulness state distribution occurred: in the remaining light period (18.00–21.00) there was noted the rapid eye movement (REM) sleep "rebound" (the increase of its amount) during the first day as well as during the second one after the influence. Similar changes of REM sleep occurrence were observed on the background of the wakefulness amount decrease. As for slow-wave sleep (SWS), neither after the first nor after the second RCE series the total time of animal being in this state did not differ from the control level. Furthermore, the significant increase of SWS episode duration was observed on the background of their amount decrease during the light as well as during the dark period. During recovery period (the next day after finishing the 2nd RCE series) the dynamics of SWS occurrence did not differ from the control. The first hours of light period were characterized by the elevated REM sleep amount. The decreased amount of REM sleep was observed in the night time due to increase of wakefulness. Nevertheless, the total time spent by animals in different functional states during the light as well as during the dark period did not differ from the control indices testifying to preservation of functional activity of brain systems involved in sleep regulation after RCE.